International standard 220 in the quality control of financial audits in ordinary civil societies - Curiñahui-Ingaroca, Anyela J. (2019)
The investigation aimed to describe the application of International Audit Standard 220, in the quality control of the audit of the financial statements carried out by two Ordinary Civil Societies of the city of Huánuco. The study was quantitative approach, applied, simple descriptive type. The sample population was selected not probabilistically made up of 40 employees of two Campos and Ramón companies, 20 of each. The survey technique and documentary analysis were applied. A checklist and a previously validated and reliable questionnaire were used. Ethical considerations were taken into account. The descriptive analysis of qualitative character with measures of central tendencies was carried out. In the results it was obtained that a quarter of the sample (25%) applied the international standard of audit 220 which establishes professional standards and legal and regulatory requirements, appropriate depending on the circumstances. However, 47.5% had a favorable opinion of its feasibility of application. It is concluded that the Ordinary Civil Societies, apply in low percentages the International Standard 220, in the quality control of financial audits of the companies, so it deserves its dissemination and generalization in order to issue reports without qualifications.